Translation of trustworthiness signals into factors for stakeholder value cocreation. Issue 3 (27th October 2017) - Castro‐Martinez, Marcelo P.; Jackson, Paul R.
Abstract : In this empirical paper, we contribute to this special issue on "The Marketing and Public Affairs of Sustainability" by addressing value creation, the raison d'être for the marketing scholarship, from a social sustainability perspective. Our evidence shows that during the interlinked practices of a focal organization and its external stakeholders, the practices from the former emit trustworthiness signals which translate into factors for stakeholder value for the latter, as precursor to stakeholder value cocreation or value destruction. Therefore, utility is not the result of an organization's decision‐making and actions but rather, it is shaped by these interlinked practices, moderated by each stakeholder group's dynamic reference state. We believe that our explanatory model, by showing that trustworthiness and stakeholder engagement are endogenous to value creation, is consistent with the view of corporate sustainability as a persuasive and effective organizational management idea.